Extended Thinking among Kindergarten Teachers - Assis. Lect. Ghufran Adnan Nasser Saloumi; Assis. Lect. Zahraa Bahjat Ezzat Othman (Journal of College of Education, 2026)
The current research aims to identify extended thinking among kindergarten teachers and to reveal the significance of differences in extended thinking according to years of service (3-5 / 5-10). To achieve the research objectives, the researcher followed the descriptive approach. The research community consisted of kindergarten teachers in the Wasit Education Department, and the research sample amounted to (150) teachers. After using statistical methods, the researcher reached the following results: - Kindergarten teachers enjoy extended thinking, and there are no differences in extended thinking among teachers according to years of service.From the previous results, the researcher reached the following recommendations and proposals: The researcher recommends that the Kindergarten Department in Iraq, in its preliminary studies, develop an extended thinking course, and that its vocabulary be developed by a general committee of measurement and evaluation professors and those specializing in kindergarten.
Keywords: extended thinking, kindergarten teachers